THE CONTENT OF THE DEVELOPMENT OF STUDENTS' IDEAS ABOUT THE SOCIO-MORAL IDEAL (Scientific journal of the Fergana State University, 2024)
In this article, the content and essence of the development of students' perceptions of the social and moral ideal is explained, and the fact that moral rules and requirements form the value base of the society formed over the centuries and the relevance of the formation and development of a common characteristic is justified.